Diyabet ve Diyabetik Ayak Eğitiminde Teknoloji - Mobil Eğitim - (:unkn) unknown (My University, 2017)
Diabetes Mellitus (DM), insülin eksikliği ya da insülin etkisindeki defektler nedeniyle organizmanın karbonhidrat, yağ ve proteinlerden yeterince yararlanamadığı, sürekli tıbbi bakım gerektiren, kronik bir metabolizma hastalığıdır. DM; giderek artan sıklığı, izlem ve tedavisinin kontrolsüz kaldığı durumlarda mortalite ve morbiditeyi artırıcı akut ve kronik komplikasyonlara yol açması, bireye ve topluma getirdiği ekonomik yükler nedeniyle önemli bir sağlık sorunudur. Diyabetin komplikasyonları arasında en sık karşılaşılanlardan biri de diyabetik ayaktır. DM, amputasyon riski dışında, morbiditenin artmasına, hastaların yaşam kalitelerinin bozulmasına ve yüksek tedavi maliyetlerine neden olan önemli bir sosyoekonomik sorundur.   Diyabet, diyabetik ayak bakımı ve koruyucu önlemlerin alınması hastanın yaşam boyunca sürdürmesi gereken bir durumdur. Bireyin bakımı kendisinin yönetmesi, yaşam şekli değişikliği haline getirmesi ve günlük ayak bakım sorumluluğunu üstlenmesi gerekmektedir. Bu nedenle diyabette eğitim büyük önem göstermektedir

Diabetes mellitus (DM) is a chronic metabolic disease which the organism cannot benefit from carbohydrates, oils and proteins adequately because of the insulin deficiency or defective function of insulin and requires continuous medical care. DM is an important health problem because of its increasing frequency, and acute and chronic complications that increase mortality and morbidity when its follow-up and treatment is out of control and economic burden placed by it on individuals and society. Diabetic foot is one of the most frequently encountered complications of diabetes. Apart from the risk of amputation, increased morbidity, is a major socio-economic problems that cause deterioration of the quality of life of patients and higher treatment costs.   Diabetes, diabetic foot care and taking preventive measures is a situation that patient should maintain throughout his/her life. The person should manage diabetic care by him/herself, make lifestyle changes and undertake the responsibility of daily foot care.   The use of technology in education is an important opportunity in terms of meeting the needs. The education related to diabetic health care, diabetic foot care prepared in accordance with the developments in technology and mobile applications for protective measures as an alternative to the conventional training; is quite important with regard to easy access to the information by patients managing their own foot care and their self-sufficiency. This article emphasizes the importance of technology and mobile education developed for diabetic persons
Technology in Diabetes and Diabetic Foot Education - Mobile Education
Keywords: Sağlık Bilimleri ve Hizmetleri; Pediatri; Temel Sağlık Hizmetleri